Historisitas Perkembangan Tafsir Pada Masa Kemunduran Islam: Abad Kesembilan dan Kesepuluh Hijriyah - Eko Zulfikar (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
This article aims to review the historicity of the development of interpretations in the ninth and tenth centuries of the Islamic era. In this century, the activities of interpreting the Qur’an based on historical quotations from friends, tabi’in and also tabi’-tabi’in were almost not enforced, because the interpreters in applying the fruit of their interpretation of the Qur’an used a scientific approach language and scientific reasoning. By using descriptive-analytical methods and pure literature studies with a content analysis approach, this paper concludes that; (1) the source of the interpretation combines the interpretations of bi al-ma’tsur and bi al-ra’yi; (2) how to explain using bayani; (3) the breadth of the explanation of the majority using the ijmali method; (4) the objectives and order of the verses use the tahlili method; and (5) the tendency of the flow in its interpretation to use linguistic aspects, namely lughawi.